POSSIBILITIES OF ARTIFICIAL INTELLIGENCE IN COMPUTER-AIDED DESIGN OF STAINED GLASS ART - Petrushevskyi, Andrii; Antonovych, Yevhen (Theory and practice of design, 2024)
Abstract. The article discusses the possibilities of artificial intelligence (AI) in the computer design of stained glass windows. Stained glass art has a long history, dating back to Ancient Rome. In the Middle Ages, stained glass became an integral part of Gothic architecture, and during the Renaissance it gained wide popularity in secular interiors. Nowadays, stained glass is used in various fields: from architecture to fashion. Modern technologies make it possible to create stained glass using various methods, including classic stained glass, Tiffany, fusing, sandblasting and others. However, the process of creating stained glass remains labor-intensive and requires highly qualified craftsmen. AI can help automate routine tasks and open up new avenues for creative expression. The article identifies tasks that are difficult for humans to perform and that can be successfully assigned to specially trained neural networks. The conditions for creating a professional system for designing stained glass canvases based on artificial intelligence have been clarified. The purpose. The aim of the article is to explore and uncover the possibilities of applying artificial intelligence in stained glass computer design. The article aims to identify the potential advantages of intelligent systems in creating and optimizing stained glass designs, particularly in analyzing and processing large volumes of data, automating the design process, enhancing accuracy and speed of development, as well as improving the functionality and aesthetic appearance of the final product. Additionally, the article seeks to highlight potential challenges and limitations in the application of artificial intelligence in this field and to point out directions for further research and technology development. Methodology. The following methods were used in the study: 1) analytical method by which the literature was analyzed; 2) theoretical and conceptual method, which allowed to determine the conditions necessary for the introduction of IT technology in cultural and artistic practice; The study used methods of computer modeling and analysis, which increased the accuracy of the results. Results. It has been determined that the application of artificial intelligence in stained glass computer design can significantly streamline and enhance the process of developing stained glass panels. The scientificance novelty The analysis of artificial intelligence capabilities in the form of automated algorithms for the development and optimization of stained glass design is a new research direction. Practical significance. With machine learning algorithms, artificial intelligence can generate unique and creative stained glass designs, taking into account contemporary trends and individual preferences of clients.